KONTRIBUSI DISIPLIN KERJA DAN BUDAYA ORGANISASI TERHADAP EFEKTIVITAS KERJA GURU PADA SMP NEGERI 2 BANGKINANG KOTA KABUPATEN KAMPAR - Hafizah Hafizah; Azhar Azhar; Murni Baheram (Universitas Riau, 2017)
The purpose of this study was to analyze the contribution of labor disciplineand organizational culture on the effectiveness of teachers’ work in SMP Negeri 2Bangkinang City Kampar regency. The population with the number of 64 teachers usingsaturation sampling technique. Samples are 64 respondents. Data were obtained fromquestionnaires or questionnaire using Likert scale. Analysis of data using multipleregression analysis using SPSS. Results from the study showed that: (1) there is a positivecontribution to the discipline of work on the effectiveness of the work of teachers of0.206 with a contribution of 20.6%. (2) there is a positive contribution betweenorganizational culture on the effectiveness of teachers’ work at .501 with a contributionof 50.1%. (3) there is a positive contribution to the discipline of work and organizationalcultures together on the effectiveness of teachers’ work at .552 with a contribution of55.2%. The conclusion of the variables contributing work discipline and organizationalculture on the effectiveness of teachers’ work has a positive direction.